(untitled) (Research, Society and Development, 2020)
The occupation of micro and small companies (MSEs) in the country’s economy has grown every year, which further highlights the importance of these companies for the country’s economic and social growth. In addition to generating a significant portion of GDP and being responsible for a large portion of formal jobs, MSEs have contributed to the development of numerous sectors and economic segments, in addition to providing opportunities for people with an entrepreneurial spirit to offer products and services that meet a significant portion of population. Regarding consultancy programs, training and monitoring of MSEs, SEBRAE in partnership with CNPQ has promoted the Local Innovation Agents Program (ALI) which aims to promote the continued practice of innovation in MSEs carried out systematically by trained scholarship holders. SEBRAE that operate in a group of companies previously selected by SEBRAE. The purpose of this article is to present an overview of the results achieved by local innovation agents in the ALI Program in the Ribeirão Preto region in the 2015-2017 triennium. The methodology used in the present work was the application of the Innovation Radar Tool, where the company is evaluated in several dimensions and later an innovation plan and monitoring of the actions to be implemented is made. The results obtained show a significant improvement in the performance indicators in several areas of the program companies, which corroborates the importance of maintaining the ALI program as an economically viable alternative for the promotion of innovation in Micro and Small Companies.